Peran Ma’had Al-Zaytun dalam Membangun Kembali Budaya Maritim Indonesia Perspektif Undang-Undang Nomor 32 Tahun 2014 dan Hukum Islam - Achmad Rizal Maulana; Abdur Rahim; Munawir Sajali (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
Indonesia has a land area of 1,919,440 km², comprising 17,508 islands, with a total territory of 5,193,250 km², including maritime and exclusive economic zones. This maritime potential supports the country's abundant natural resources. This study aims to examine the role of Ma’had Al-Zaytun in revitalizing Indonesia's maritime culture based on Law Number 32 of 2014 and Islamic Law. The research employs a normative juridical approach, using primary data sources such as Law Number 32 of 2014, the book Fiqh al-Bi’ah (Environmental Jurisprudence), and other related literature. The findings indicate that Ma’had Al-Zaytun plays a significant role in the vision of Indonesia's maritime culture. The institution integrates a maritime curriculum, including a program for Maritime Vocational Islamic High Schools, to enhance students' understanding of maritime heritage. Ma’had also established the Samudra Biru Port as a learning facility and a means to manage post-harvest marine products, supporting ecological practices based on Fiqh al-Bi’ah. This approach aligns with Islamic law, which promotes environmental preservation for communal welfare. The development of fishing vessels and marine product management reflects the institution's commitment to sustainable maritime resource stewardship. Thus, Ma’had Al-Zaytun serves as a model for integrating education and resource management in line with Islamic legal principles.